Antiproliferative and pro-apoptotic effects of Pseudevernia furfuracea (L.) Zopf extract and its active component physodic acid via oxidative stress and DNA damage in breast cancer cells - Sebova, Dominika; Zilakova, Simona; Medvecova, Viktoria; Goga, Michal; Frenak, Richard; Bardelcikova, Annamaria; Mirossay, Andrej; Mirossay, Ladislav; Mojzis, Jan; Kello, Martin (Frontiers in Oncology, 2025)
BackgroundMammary gland malignancies are the most diagnosed oncological diseases in women. The currently available treatment faces several problems, including resistance to cytostatics and the relatively high recurrence rates. These limitations have led to an increasing interest in natural substances as potential anticancer agents. Therapeutic approaches using a combination of natural anticancer agent and conventional cytostatic drug could also be beneficial in minimising the risk of chemotherapy. In the present study, we evaluated the anticancer effect of Pseudevernia furfuracea (L.) Zopf extract (PSE) and isolated the secondary metabolite physodic acid (PHY) in in vitro models of breast cancer subtypes (ER+, HER2+, and triple negative).MethodsTo investigate the effects of tested compounds, a range of assays were employed. BrdU and clonogenic assays were used to evaluate antiproliferative activity. Flow cytometry and Western blot were used to demonstrate apoptotic cell death, oxidative stress, DNA damage, and immune checkpoint modulation in a time-dependent manner (24, 48, and 72 h).ResultsPSE and PHY induced cycle arrest at a G1 checkpoint with modulation of cell cycle-related proteins. Furthermore, activation of intrinsic apoptotic pathway, involving changes in Bcl-2 family proteins, caspase-3/-7 activity, caspase-9 cleavage, cytochrome c release, and PARP cleavage, was detected in all BC cells. Moreover, we determined the PSE- and PHY-mediated generation of ROS and RNS, which led to DNA damage and the activation of the DNA damage response.ConclusionsTreatment with PSE and PHY in BC cells resulted in mitochondrial apoptosis associated with oxidative stress and DNA damage. Furthermore, modulation of immune checkpoint PD-1/PD-L1 was demonstrated. Based on the results, we assume the use of PSE and PHY as promising targeted agents for BC.